Quantitative determination of colistin A/B and colistin methanesulfonate in biological samples using hydrophilic interaction chromatography tandem mass spectrometry. Issue 8 (5th June 2020) - Qi, Bing; Gijsen, Matthias; Van Brantegem, Pieter; De Vocht, Tom; Deferm, Neel; Abza, Getahun B.; Nauwelaerts, Nina; Wauters, Joost; Spriet, Isabel; Annaert, Pieter
Abstract: Colistin (polymyxin E) is a polycation antibiotic which is increasingly used (administered as colistin methanesulfonate, CMS) as a salvage therapy in critically ill patients with multidrug resistant Gram‐negative infections. Even though colistin has been used for more than 50 years, its metabolic fate is poorly understood. One of the current challenges for studying the pharmacokinetics (PK) is the precise and accurate determination of colistin in in vitro and in vivo studies. In the present study, we developed and validated a series of sensitive and robust liquid chromatography tandem mass spectrometry (LC–MS/MS) methods for analysing biological samples obtained from in vitro and in vivo disposition assays. After a zinc acetate‐mediated precipitation, hydrophilic–lipophilic‐balanced solid phase extraction (HLB‐SPE) was used for the extraction of colistin. The compounds were retained on a hydrophilic interaction liquid chromatography (HILIC) column and were detected by MS/MS. CMS was quantified by determining the produced amount of colistin during acidic hydrolysis. The developed methods are sensitive with lower limits of quantification varying between 0.009 μg/mL and 0.071 μg/mL for colistin A, and 0.002 μg/mL to 0.013 μg/mL for colistin B. The intra‐ and inter‐day precision and accuracy were within ±15%. Calibration curves of colistin were linear (0.063 μg/mL to 8.00 μg/mL) within clinically relevant concentration ranges. Zinc acetate‐mediated precipitation and the use of a HILIC column were found to be essential. The developed methods are sensitive, accurate, precise, highly efficient and allow monitoring colistin and CMS in biological samples without the need for an internal standard. Abstract : Quantitative bioanalytical methods were developed and validated to study the PK of colistin. Zinc acetate precipitation was essential for SPE and generating a high recovery. A HILIC–type column was confirmed to be an excellent choice for colistin analysis.